Unveiling the mythical candles. (February 2020) - Jou, Jwo-Huei; Wu, Chun-Hua; Su, Yu-Ting; He, Zhe-Kai; Dubey, Deepak Kumar; Tsai, Yi-Fang; Song, Wei-Chi; Zeng, Hao-Tian
Abstract: Candles were invented 5000 years ago and are still widely adopted in numberless occasions to illuminate the buildings and to create a romantic environment due to their warm and pleasant sensation giving emission, which helps people relax. Nevertheless, some myths remain unsolved regarding their color, color temperature, power efficiency, their effects on human health, and fire hazard. We have hence investigated these based on a paraffin wax candle. As learned experimentally, the flickering candle flame shows on average an orange-red color with Commission Internationale de l'Eclairage 1931 coordinates of (0.55, 0.41) and a 1819 K color temperature through observation behind a tracing paper. Although the luminous intensity may vary from 1.0 to 2.2 cd, the luminous efficacies of studied candles fall around 0.27 l m/W. From a retina protection perspective, candlelight is presumably 2 times safer than the typical incandescent bulb or warm-white compact fluorescent lamp (CFL), and 3 times safer than the warm-white light-emitting diode (LED). Correspondingly, if used at night, it is about 2 times better for melatonin secretion than the incandescent bulb or warm-white LED, and 3 times better than the warm-white CFL. However, surprisingly, candlelight-style organic light-emitting diode (OLED) is healthier than real candlelight: from retina protection and melatonin secretion perspective, the candlelight style OLED is about 3 times safer and 2 times better than candlelight, respectively. While the luminous intensity may sensitively vary with the variation of wax as well as wick material and size, the candle color and color temperature barely alter with different compositions. Highlights: Candles provide warm and pleasant sensation due to their soft orange-red emission. Luminous intensity may vary with the variation of wax, wick material and size. Candlelight is 2 and 3 times safer than the warm-white CFL and LED, respectively. OLED is healthier than candlelight from retina and melatonin secretion perspective.